SLAUGHTER VALUE OF PIGS CARCASSES AS RELATED TO COLIPASE GENOTYPE (CLPS) CONSIDERING RYR1 GENE EFFECT - Hanna JANKOWIAK; Wojciech KAPELAŃSKI; Milena BIEGNIEWSKA (Journal of Central European Agriculture, 2009)
The experiment was carried out on 110 3-breed crossbreds fatteners [♂ Pietrain x (♀ Polish Large White x Polish Landrace)]. Pigs were reared in standard conditions and slaughtered at an average body weight of 105 kg. Gene polymorphism was determined with the PCR-RFLP procedure (CLPS/DdeI and RYR1/HinPI). One day postslaughter, the right carcass-sides were dissected and evaluated using the methods applied for the Polish Pig Testing Station (SKURTCh). The study evaluated the slaughter value of carcasses depending on colipase genotype (CLPS) with infl uence of major gene RYR1. Colipase gene differentiated carcass lean content only in RYR1CC pigs and in all pigs the neck weight as well as its tissue composition in RYR1CT pigs. Moreover, signifi cant infl uence of major gene (RYR1T) on quantitative traits was confi rmed.